Особенности фауны Личинок трематод—паразитов пресноводных моллюсков Крыма - Стенько, Р.П. (Вестник зоологии, 1979)
Distribution of the trematoda larvae in certain water bodies and zones is considered and the fauna of the trematode larval forms is analyzed in comparison with that of the Ukraine as a whole. In freshwater molluscs of the Crimea 37 species of parthenits, cercarii and metacercarii are registered. in molluscs inhabiting other water bodies of the Ukraine 152 species were found according to the data of V. I. Zdun (1961).